Ashy Dermatosis – A rare case in a 7year old Indian male childAshy Dermatosis – A rare case in a 7year old Indian male child - B Sandeep; P Shefali; B Kiran; Namitha (Pediatric Review: International Journal of Pediatric Research, 2022)
Ashy dermatosis also known as erythema dyschromicum perstans, is an acquired chronicpigmentary skin disorder. This disorder has been very rarely reported in Indian children. Here wereport a case of a 7year old male child presented to pediatrics OPD with multiple areas ofhyperpigmentation. A skin biopsy was done which was suggestive of Ashy dermatosis. Earlyrecognition of this condition is important for proper diagnosis and to prevent unnecessaryinvestigations.